PERIKHORESIS ALLAH TRINITAS SEBAGAI PARADIGMA RELASI GEREJA DALAM KONTEKS KEMAJEMUKAN AGAMA DI INDONESIA - Patty, Lidya (Publisher: Bethel Press; Unit Penerbit: STT Bethel Indonesia Jakarta, 2025)
Indonesia, as a plural society, often faces tensions among religious communities, challenging the church to offer a constructive paradigm of interfaith relations. This study aims to interpret the concept of perichoresis of the Triune God as a relational model for the church in engaging with other religions in the Indonesian context. The method employed is a literature-based study with a constructive theological approach, integrating classical and contemporary sources (Thomas Aquinas, Jürgen Moltmann, Joas Adiprasetya, and others) that discuss perichoresis and relational theology. Through this exploration, the study formulates three pillars of interfaith praxis—equality, openness, and cooperation—derived from the principle of perichoresis. The findings show that (1) perichoresis provides a relational framework that affirms religious identity without subordination; and (2) the paradigm of perichoresis offers an alternative to pluralist or inclusivist models by affirming both unity and difference. Thus, the study concludes that Trinitarian theology, when read through the lens of perichoresis, can contribute concretely to interreligious relations in Indonesia.